Kāyagatāsati Bhāvanā: The Cultivating Subjective Process of Arousing Mental State - Ounephaivong, Somsak; Acharashubho Thepa, Phrakhrupalad Chakrapol; Chayawuddho Pettongma, Phrakhruwuttichaikrankroson Wutthichai (วารสารบัณฑิตศาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2025)
Consideration of the body according to the Four Foundations of Mindfulness involves establishing mindfulness in relation to the body. This includes being aware, observing, knowing, and seeing the body as it truly is. It involves observing the body to see its arising and its inevitable decay, and firmly anchoring one’s mindfulness in the body with a sense of detachment. It is not about clinging to the body but recognizing its existence for the sake of understanding the truth. When considering the body in this way, all cravings and wrong views gradually diminish, and one becomes transparent, free from any firm grasping of anything in the world. There are six categories for the practical application of this approach: The category of in-and-out breathing refers to establishing mindfulness of the breath, being aware of the breath as it naturally occurs, and ceases (rises, falls) in its ordinary course. The category of postures refers to establishing mindfulness in various bodily postures on walking, standing, sitting, lying down. It involves being aware of any bodily posture as it naturally occurs and ceases (arises, changes) in its ordinary course. The category of activities refers to establishing mindfulness in daily activities, including activities such as walking, stepping, looking, eating, drinking, speaking, and excreting. It involves being aware of these activities as they naturally occur and cease (arise, change) in their ordinary course. The category of repulsiveness of the body refers to establishing mindfulness by recognizing the body as something repulsive, composed of hair, nails, skin, and so on. It involves being aware of this body from the soles of the feet to the crown of the head, realizing that it consists of various internal and external organs that arise and eventually decay (arise, change) in their ordinary course. The category of elements refers to establishing mindfulness by recognizing the four elements: earth, water, fire, and air. It involves being aware of the body in terms of these four elements, realizing that they arise and eventually cease (arise, change) in their ordinary course. These are the six categories for the practical application of mindfulness in relation to the body.